Establishment of Human Pluripotent Stem Cell‐Derived Skin Organoids Enabled Pathophysiological Model of SARS‐CoV‐2 Infection. Issue 7 (31st December 2021) - Ma, Jie; liu, Jia; Gao, Dunqin; Li, Xiao; Zhang, Qiyu; Lv, Luye; Wang, Yujie; Li, Jun; Zhu, Yunping; Wu, Zhihong; Hu, Hengrui; Li, Yufeng; et al.
Abstract: Coronavirus disease 2019 (COVID‐19) patients with impact on skin and hair loss are reported. Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is detected in the skin of some patients; however, the detailed pathological features of skin tissues from patients infected with SARS‐CoV‐2 at a molecular level are limited. Especially, the ability of SARS‐CoV‐2 to infect skin cells and impact their function is not well understood. A proteome map of COVID‐19 skin is established here and the susceptibility of human‐induced pluripotent stem cell (hiPSC)‐derived skin organoids with hair follicles and nervous system is investigated, to SARS‐CoV‐2 infection. It is shown that KRT17+ hair follicles can be infected by SARS‐CoV‐2 and are associated with the impaired development of hair follicles and epidermis. Different types of nervous system cells are also found to be infected, which can lead to neuron death. Findings from the present work provide evidence for the association between COVID‐19 and hair loss. hiPSC‐derived skin organoids are also presented as an experimental model which can be used to investigate the susceptibility of skin cells to SARS‐CoV‐2 infection and can help identify various pathological mechanisms and drug screening strategies. Abstract : A proteome map of coronavirus disease 2019 skin is established. A human‐induced pluripotent stem cell‐derived skin organoids model is constructed and used to show that KRT17+ hair follicles and different types of nerve cells can be infected by severe acute respiratory syndrome coronavirus 2 and are associated with the impaired development of hair follicles and epidermis.